How does reorganisation in child and adolescent mental health services affect access to services? An observational study of two services in England - Fazel, M; Rocks, S; Glogowska, M; Stepney, M; Tsiachristas, A (Public Library of Science, 2021)
Background Child and Adolescent Mental Health Services (CAMHS) in England are making significant changes to improve access and effectiveness. This ‘transformation’ variously involves easier access to services through a Single Point of Access (SPA), more integrated services within CAMHS and enhanced co-provision across education and third sector or non-profit organisations.